(untitled) (Research, Society and Development, 2020)
The Human Resource area is considered one of the most important in organizations, whether public or private. Within this area there are several tools used to promote and recognize human capital. One of these techniques is Competency Management which consists of understanding what are the organizational competencies critical to business success, deploying them in terms of professional competences and developing them with the internal staff. Considering this context, this article aims to elaborate the competence matrix for the Maintenance Planning and Control department of an ore processing plant. To achieve this objective, a survey was carried out regarding the skills of the professionals responsible for technical inspections in relation to the technical demands offered by the equipment used. To this end, a questionnaire was developed, in which employees described the degree of compliance with which they are in relation to certain activities and equipment. As a result of the work, a deficit of competence was found, in general, with the need for training and knowledge management within the department studied.